Eccezione e Stato costituzionale democratico. Una incompatibilità strutturale (Società e diritti, 2023)
AbstractContemporary societies seem to be unable to emerge from the emergency condition. The advent of an order of human relations marked by growing material well-being and an increasingly marked cultural homogeneity, in the direction of a cosmopolitan construction, now seems like a failed project. Many observe that the constant recourse to government instruments justified by situations of necessity constitutes an objective element of transformation of the institutional structures of liberal democracies, which in reality thus demonstrate a tendency towards authoritarian logics to manage the conflict that increasingly disturbs contemporary communities. Rather than refusing to use the category of state of exception as a concept capable of capturing part of the ongoing processes, it is appropriate to underline its relevance. At the same time and precisely for this reason, it appears necessary to clearly reject the continuation of extraordinary administrative actions, self-legitimizing with the evocation of the exceptional condition.Because they are not compatible with the principles of constitutional democracies. Not only because they are in contrast with the rule of law model but because, even more, they lead to a real suffocation of the democratic process